Main parameters of a wastewater treatment plant up to 2000 PE in the Czech Republic - Hluštík, Petr (IOP Publishing, 2020)
The article deals with optimising the design parameters of wastewater production and specific pollution production in wastewater treatment plants up to 2,000 PE. The objective of this article is to determine more precise design values applicable to WWTP calculations and different drainage systems on the basis of statistical evaluation of individual water quality indicator analyses.

The article deals with optimising the design parameters of wastewater production and specific pollution production in wastewater treatment plants up to 2,000 PE. The objective of this article is to determine more precise design values applicable to WWTP calculations and different drainage systems on the basis of statistical evaluation of individual water quality indicator analyses.
Main parameters of a wastewater treatment plant up to 2000 PE in the Czech Republic
Keywords: wastewater treatment plant; design parameters; wastewater quality; wastewater treatment plant; design parameters; wastewater quality